A - Saifudin Saifudin; Maulynda Arifah Rahmawati (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
The study aimed to analyze the implementation of digitalization of tax administration in order to improve taxpayer compliance in Semarang Selatan Tax Office.The study used qualitative methods of case study, with data collection using in-depth interview techniques, direct observation and documentation. To test the credibility of data, it used triangulation of data sources. The source of the study data in-depth interview was participant who have a position or authority on the object of the study, namely as many as three participants based on the principles of appropriateness and adequacy.The results of this study showed that the digitalization of tax administration has been implemented in every business process in Semarang Selatan Tax Office. The implementation of digitalization has not been able to improve taxpayer compliance in 2018-2020. Based on the supporting and inhibiting factors, there are several things that need to be considered by Semarang Selatan Tax Office to achieve high taxpayer compliance include ensuring the ease of taxpayer services, optimizing digitalization of every business process, and optimizing 3C service schemes (Click, Call, and Counter).